Early development of olfactory circuit function - Maier, Joost X.; Zhang, Zihao (Frontiers in Cellular Neuroscience, 2023)
During early development, brains undergo profound changes in structure at the molecular, synaptic, cellular and circuit level. At the same time, brains need to perform adaptive function.How do structurally immature brains process information? How do brains perform stable and reliable function despite massive changes in structure? The rodent olfactory system presents an ideal model for approaching these poorly understood questions. Rodents are born deaf and blind, and rely completely on their sense of smell to acquire resources essential for survival during the first two weeks of life, such as food and warmth. Here, we review decades of work mapping structural changes in olfactory circuits during early development, as well as more recent studies performing in vivo electrophysiological recordings to characterize functional activity patterns generated by these circuits. The findings demonstrate that neonatal olfactory processing relies on an interacting network of brain areas including the olfactory bulb and piriform cortex. Circuits in these brain regions exhibit varying degrees of structural maturity in neonatal animals. However, despite substantial ongoing structural maturation of circuit elements, the neonatal olfactory system produces dynamic network-level activity patterns that are highly stable over protracted periods during development. We discuss how these findings inform future work aimed at elucidating the circuit-level mechanisms underlying information processing in the neonatal olfactory system, how they support unique neonatal behaviors, and how they transition between developmental stages.